PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 09 KOTO BARU - Meilani Khasanah, Alfi; Ningsih Almirus, Ayu; Ali, Gunawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low Mathematics learning outcomes of fifth-grade students at SDN 09 Koto Baru, as indicated by the large number of students who had not yet achieved the Learning Objective Achievement Criteria (KKTP). This condition was influenced by a teacher-centered learning process, students who easily became bored and were occupied with their own activities during the learning process, students who were passive and less interactive when responding to the teacher's questions, and students who frequently entered and left the classroom, disturbing their classmates. One effort to overcome these problems is by implementing the Teams Games Tournament (TGT) learning model. This study aimed to determine the effect of the Teams Games Tournament (TGT) learning model on the Mathematics learning outcomes of fifth-grade students at SDN 09 Koto Baru.This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The study was conducted at SDN 09 Koto Baru and involved 17 fifth-grade students as the research participants. Data were collected through learning achievement tests consisting of a pretest and a posttest. The data were analyzed using the Shapiro–Wilk normality test and the Wilcoxon signed-rank test with the assistance of SPSS version 25.The results showed that the implementation of the Teams Games Tournament (TGT) learning model had a significant effect on the Mathematics learning outcomes of fifth-grade students at SDN 09 Koto Baru. This was indicated by an increase in the students' mean score from 57.94 on the pretest to 78.23 on the posttest. Furthermore, the hypothesis test produced a significance value of 0.000, which was lower than 0.05 (0.000 < 0.05). Therefore, the alternative hypothesis (Ha) was accepted, while the null hypothesis (H₀) was rejected. It can be concluded that the Teams Games Tournament (TGT) learning model has a significant positive effect on improving the Mathematics learning outcomes of fifth-grade students at SDN 09 Koto Baru.